Kinetic study and thermodynamic equilibrium modeling of the Co(II) and Mn(II) bioadsorption using the Rhodococcus opacus strain - Valdiviezo Gonzales, Lorgio (2022)
Microbial biomass is considered a renewable and environmentally friendly resource. Thus, the research conducted a kinetic study and thermodynamic equilibrium modeling of the cobalt (Co) and manganese (Mn) bioadsorption process using the Rhodococcus opacus (RO) strain as a biosorbent. The inactive biomass subjected to 0.1 M NaOH pretreatment was brought into contact with synthetic solutions of Co and Mn. The experimental data for the Co(II) and Mn(II) bioadsorption process were fit to the Langmuir model with kads of 0.65 and 0.11 L.mg-1, respectively. A better statistical fit was also obtained for the pseudo-second order kinetic model (R2Co(II) = 0.994 and R2Mn(II) = 0.995), with 72.3% Co(II) and 80% Mn(II) removals during the first 10 min. In addition, a higher affinity of RO for the Co(II) ion was observed, with maximum uptake values of 13.42 mg.g-1; however, a higher adsorption rate was observed for Mn(II) ion (k = 0.21 g.mg-1.min-1 at 318 K). The bioadsorption process was spontaneous and dependent on temperature, being endothermic and irreversible for the Co(II) ion (∆H = 2951.91 J.mol-1) and exothermic and reversible for the Mn(II) ion (∆H = -2974.8 J.mol-1). The kinetic and thermodynamic equilibrium modeling allowed to identify the main mechanisms involved in the biosorption process of both metals.